Teaching English Tenses in EFL Environment Through Jeopardy Game: A Game-Based Learning Approach to Second Language Acquisition - Wati, Rina; Bunau, Eusabinus; Rahmani, Eka Fajar; Sudarsono, Sudarsono; Husin, Syarif (Pascasarjana Universitas Negeri Makassar, 2023)
Educational methodologies have continually evolved to accommodate the diverse needs of learners. One such evolution has seen the rise of game-based learning, aiming to make education more interactive and engaging. This research focused on determining the efficacy of the Jeopardy game in enhancing the understanding of the simple present tense among seventh-grade students at SMP Negeri 7 Sungai Ambawang during the Academic Year 2022/2023. Using a pre-experimental research design, this study delved into the potential advantages of game-based learning over traditional teaching methods. A sample size of 25 students from class VII A was meticulously chosen to ensure the results' consistency and accuracy. To measure the students' grasp of the simple present tense both before and after the Jeopardy game intervention, a multiple-choice test, consisting of 20 items, was administered. Each item in the test offered four options (a, b, c, and d) for students to choose from. Statistical analysis of the gathered data resulted in compelling outcomes. The null hypothesis (H0), which posited that the Jeopardy game would have no significant impact on the students' understanding of the simple present tense, was soundly rejected. In contrast, the alternative hypothesis (Ha), suggesting the game's effectiveness, was accepted. This conclusion was bolstered by a notable t-value of 9.62, surpassing the critical t-table value of 2.064 at 24 degrees of freedom with a 5% significance level. Furthermore, the study highlighted a strong effect size of 1.9, indicating the game's substantial impact on learning.